Comparative Evaluation of Pork-Specific Primer Sets for Detecting Pork DNA in Commercial Meat-based Seasonings by Species-Specific PCR - Nur Atiqah, Khairul Adha; Lesley Maurice, Bilung; Awang Ahmad Sallehin, Awang Husaini; Aida Azrina, Azmi (Universiti Malaysia Sarawak, 2026)
Food adulteration remains a critical issue in halal food authentication, particularly for highly processed foods. During food processing, exposure to heat, chemicals, and physical treatments often degrades DNA and alters the food matrix, thereby reducing the effectiveness of species identification methods. Despite the widespread application of the Polymerase Chain Reaction (PCR), data on the detection of pork DNA in complex food products such as food seasonings remain limited. Previous studies have reported that amplicon length influences primer performance. Therefore, this study was conducted to evaluate the specificity and sensitivity of species-specific primers with different amplicon lengths for detecting low concentrations of pork DNA in binary meat mixtures, screening for potential pork adulteration in highly processed seasoning products, and assessing the applicability of pork-specific primers as a screening tool for halal authentication. The DNA was extracted from raw meat, deliberately adulterated meat, and commercial food seasoning products using the DNeasy Mericon Food kit (Qiagen, Germany). Species-specific primers targeting the mitochondrial cytochrome b gene (cytb) were used in PCR assays, producing amplicon lengths of 398, 288, and 149 bp for pork, 120 and 133 bp for bovine and chicken, respectively. Primer specificity was evaluated by testing for cross-reactivity against DNA from non-target species, while sensitivity was determined using binary mixtures of pork and other meat species. The applicability of pork-specific primers was assessed in commercial food seasoning products without halal logos, with halal-certified samples included as controls. The results showed that all primer sets exhibited high specificity with no cross-reactivity toward non-target species. Sensitivity analysis revealed that pork DNA could be consistently detected at concentrations of up to 1% in a binary meat mixture using all the pork-specific primers. Despite DNA degradation in highly processed foods, several seasoning samples yielded sufficient DNA quality and quantity for successful amplification, particularly those with a halal logo, suggesting better processing and storage conditions. Among the three pork-specific primers, the shortest amplicon length (149 bp) exhibited the highest sensitivity for detecting pork DNA, as indicated by the intense band on a 2% agarose gel. No pork DNA contamination was detected in any food seasoning product tested, including samples without halal logos. However, chicken DNA was unexpectedly detected in a pork broth cube sample and confirmed by DNA sequencing. BLASTN (Basic Local Alignment Search Tool for Nucleotides) analysis showed a 95.79% similarity, suggesting possible cross-contamination during manufacturing. Repeated testing of additional batches revealed no contamination, indicating that the chicken DNA detected was unintentional and inconsistent across batches. In conclusion, pork-specific PCR targeting the cytb is a specific, sensitive, and cost-effective method for detecting pork DNA in both raw and highly processed foods. This study highlights the importance of primer selection, particularly favouring shorter amplicons, and supports the use of species-specific PCR as a practical screening tool for halal authentication in complex food matrices.